Problem-Based Learning (PBL) in a Grade 11 World History Class: Trials, Tribulations, and Triumphs - Bruce R. Maxwell (Halla Newcastle Education and Research Center, 2020)
Purpose The purpose of this work was to describe and reflect on the worth of the iterative design of a valid teaching method for senior school level social studies classes reliant on PBL methods. Method This descriptive reflection on the implementation of a Problem-Based Learning (PBL) activity involved a small elective class of ten Grade 11 World History students at Selwyn House School (SHS), in the Canadian Province of Quebec. Use of PBL was a five-step process, involving two different classes run concurrently, once with Cohort Group #1 (2017-18) in the spring of 2018, and twice with Cohort Group #2 (2018-19). Results PBL processes evolved through three PBL examples involving twentieth-century historical situations, beginning with World War Two (1939-1945) and concluding with the Cold War (1946-1991). Design features and processes demonstrated enhanced outcomes from student-centered learning. Conclusion The particular methods produced results that were evident in the students' finished products.